Predictable, Tunable Protein Production in Salmonella for Studying Host-Pathogen Interactions - Cooper, Kendal G.; Chong, Audrey; Starr, Tregei; Finn, Ciaran E.; Steele-Mortimer, Olivia (Frontiers in Cellular and Infection Microbiology, 2017)
Here we describe the use of synthetic genetic elements to improve the predictability and tunability of episomal protein production in Salmonella. We used a multi-pronged approach, in which a series of variable-strength synthetic promoters were combined with a synthetic transcriptional terminator, and plasmid copy number variation. This yielded a series of plasmids that drive uniform production of fluorescent and endogenous proteins, over a wide dynamic range. We describe several examples where this system is used to fine-tune constitutive expression in Salmonella, providing an efficient means to titrate out toxic effects of protein production.